Cholecystectomy- Diagnostic Stratification on the Basis of Age and Sex - Naqqash Adnan ,Jahangir Sarwar Khan , Marriam Ahmed (Journal of Rawalpindi Medical College, 2016)
Background: To study the histopathological specimen of gall bladder inflammation and to correlate the pattern of inflammation with age and sex and to detect undiagnosed carcinoma of gall bladder. Method:-In this descriptive study patients undergoing laparoscopic cholecystectomy for symptomatic gall stones were included. Laparoscopic cholecystectomy was performed in all cases but had to be converted to open procedure in cases where anatomical distortion and dense adhesions prevented any further progress. Specimens were evaluated grossly and microscopic study was done. Results: Over a period of two and half years, three hundred patients with symptomatic gallstones were admitted for cholecystectomy. There were 237 females (79%) and 63 males (21%) with a male to female ratio of 1:7.9. The age ranged from 21 to 80 years(mean age=41.5 ± 5.3 years). Chronic cholecystitis was the commonest diagnosis. Adenocarcinoma was found in one patient, more than 70 years of age . Extensive gallbladder inflammation in the form of necrotizing or gangrenous cholecystitis was recorded in a significant number of male patients 5 (83.3%)compared to one female patient(16.7%). Commonest age group for chronic cholecystitis was 41-50 years age group. For acute on chronic cholecystitis, 51-60 years age group was commonest . Conclusion:-Chronic cholecystitis is the commonest presentation. Supparative cholecystitis more common in females whereas gangrenous gall bladder was detected more in males.